2023
DOI: 10.3390/biomedicines11020553
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary Dysplasia in Extremely Premature Infants: A Scoping Review for Identifying Risk Factors

Abstract: Background: Over the years, bronchopulmonary dysplasia (BPD) affects the pulmonary function of infants, resulting in chronic health burdens for infants and their families. The aim of this scoping review was to screen available evidence regarding perinatal risk factors associated with the development and severity of BPD. Methods: The eligibility criteria of the studies were year of publication between 2016 and 2021; setting of a developed country; English or Japanese as the study language; and randomized contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 74 publications
1
1
0
Order By: Relevance
“…According to a retrospective study by Smith et al (14), the incidence of BPD is signi cantly greater in twins (29.9%) than in singletons (23.6%). Another study reported similar results (15). These ndings highlight that twins face unique challenges related to foetal growth, the intrauterine environment, and delivery, which may increase the risk of BPD.…”
Section: Introductionsupporting
confidence: 58%
“…According to a retrospective study by Smith et al (14), the incidence of BPD is signi cantly greater in twins (29.9%) than in singletons (23.6%). Another study reported similar results (15). These ndings highlight that twins face unique challenges related to foetal growth, the intrauterine environment, and delivery, which may increase the risk of BPD.…”
Section: Introductionsupporting
confidence: 58%
“…One surprising finding was the statistical significance of a low APGAR score (<7) at 5 min in the BPD group but not in moderate-to-severe BPD/death groups. The impact of a low Apgar score on the development of BPD has yielded inconsistent results across studies [29,30], with the role of a low Apgar score as a risk factor for moderate-to-severe BPD/death remaining inconclusive. However, ETT or CPCR in initial resuscitation was statistical significant in moderate-to-severe BPD/death groups but not in the BPD group.…”
Section: Discussionmentioning
confidence: 99%